Analisis Strategi Kreatif Iklan @Dreamup_id Untuk Meningkatkan Penjualan Digital - Fachmi Adi Pratama; M.Arkansyah (DIGICOM : Jurnal Komunikasi dan Media, 2023)
In line with the business phenomenon that uses social media as the realm of advertising and marketing. This study aims to find out how creative strategies for Instagram @Dreamup_id social media advertising are to increase sales. Dimensions that must be researched are the design and application of creative strategies for pre-production advertising, advertising production to post-production advertising. The research method used is qualitative Robert K. Yin, with data collection through observation, interviews, and documentation. The speakers in this study were the Owner/Creative Director/Advertiser, Copywriter, Art Director/Graphic Designer who participated in making creative advertising strategies to increase sales.